Inheritance of aluminum resistance characteristics in spring wheat sprouts under conditions of a roll culture - L. V. Volkova; O. S. Amunova (Аграрная наука Евро-Северо-Востока, 2019)
Eight varieties of spring soft wheat and 16 hybrids of the second generation, formed by the method of complete top crosses have been studied in terms of the development parameters of seedlings (the length of the embryonic roots, the weight of roots and aboveground parts), and the potential resistance to aluminum ions (root length index - RLI) under conditions of a roll culture (control - distilled water, experience - an aqueous solution of aluminum sulfate at a concentration of 1.5 mmol, pH 4.3). Initial varieties are analyzed for general and specific combinational ability (GCA and SCA). High-growth parameters were characteristic of Baganskaya 95 (Russia, Novosibirsk region), Karabalykskaya 98 (Kazakhstan), Jasna (Poland); the values of the RLI are Altaiskaya 530 (Russia, Altai Territory) and Gornouralskaya (Russia, Sverdlovsk Region). Three promising hybrid combinations with a high degree of phenotypic dominance of morphological characteristics were identified (Altaiskaya 530 x Lutescens 30, Baganskaya 95 x Serebristaya, Tyumenskaya 26 x Jasna) and five hybrid combinations for resistance to stress (Altaiskaya 530 x Serebristaya, Altaiskaya 530 x Jasna, Baganskaya 95 x Lutescens 30, Karabalykskaya 98 x Lutescens 30, Tyumenskaya 26 x Serebristaya). As a result of the research, it has been shown that aluminum ions exert the greatest influence on the length of the embryonic roots, reducing it by 5...25% depending on the genotype. Variety differentiation of characters is more evident in control conditions. The total inheritance ratio (h2O) of the parameters studied was 0.61 ... 0.87, which indicated the possibility of effective selection for potential productivity and resistance to aluminum. The influence of the paternal components on the root length of the hybrids was insignificant; the values of the root length index were determined mainly by the maternal components, which should be taken into account when planning crosses involving these varieties.